Effects of chlorine disinfection on RO membrane biofouling at low feed water temperature for wastewater reclamation. Issue 4 (24th November 2022) - Yu, Tong; Sun, Shoufang; Zhao, Yunlong; Wang, Lingxue; Li, Ping; Chen, Zhuo; Bi, Xuejun; Shi, Xueqing
Abstract: Chlorine disinfection has been reported to be ineffective in controlling RO membrane biofouling in some projects. Feed water temperature is a crucial factor in the formation of RO membrane biofouling. It has a positive impact on the wide application of the RO process to ascertain whether chlorine disinfection can alleviate the membrane biofouling at low temperatures. In this study, the effects of chlorination on the RO membrane biofouling at low feed water temperature (10 °C) were investigated by a lab-scale RO apparatus. The final normalized flux was 0.33 and 0.29 with and without chlorination, respectively. According to the normalized flux decline curve, chlorination could not alleviate the RO membrane fouling at low temperature. Based on the intermediate blocking model, chlorination increased the membrane fouling potential of the feed water. At low temperature, the biofilm on the membrane with chlorination was thinner and denser than that without chlorination. In addition, the membrane with chlorination contained more foulants and dissolved organic matter than that without chlorination. Chlorination failed to continuously prevent bacteria accumulation on RO membrane at low temperature, but screened out bacteria that were potentially more suitable for the low-temperature membrane environment. HIGHLIGHTS: Effects of chlorination on RO membrane biofouling at low temperature were studied. Chlorine disinfection could not alleviate the RO membrane fouling at low temperature. The biofilm with chlorination was thinner but had more foulants at low temperature. Chlorine disinfection failed to prevent bacterial accumulation at low temperature. Chlorination changed the microbial community structure at low temperature. Graphical Abstract